2020
DOI: 10.3847/1538-4357/ab8811
|View full text |Cite
|
Sign up to set email alerts
|

The Lyman Continuum Escape Fraction of Galaxies and AGN in the GOODS Fields

Abstract: We present our analysis of the Lyman continuum (LyC) emission and escape fraction of 111 spectroscopically verified galaxies with and without active galactic nuclei (AGN) from 2.26 < z < 4.3. We extended our ERS sample from Smith et al. with 64 galaxies in the GOODS North and South fields using WFC3/UVIS F225W, F275W, and F336W mosaics we independently drizzled using the HDUV, CANDELS, and UVUDF data. Among the 17 AGN from the 111 galaxies, one provided a LyC detection in F275W at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 191 publications
4
21
0
Order By: Relevance
“…The bulk of our ionizing flux (67%) comes from the five SFGs, with the remaining galaxies contributing only a small fraction. This is consistent with the results of Smith et al (2018Smith et al ( , 2020, who do not detect significant LyC emission in their own stacking analyses. This bimodality may be caused by favorable lines-ofsight through the ISM of the host galaxy (e.g., Cen & Kimm 2015) and/or the IGM rather than by the intrinsic galaxy properties, with the small number of candidate LyC leakers corresponding to lines-of-sight with low IGM absorption.…”
Section: Contributions To the Metagalactic Ionizing Backgroundsupporting
confidence: 92%
See 1 more Smart Citation
“…The bulk of our ionizing flux (67%) comes from the five SFGs, with the remaining galaxies contributing only a small fraction. This is consistent with the results of Smith et al (2018Smith et al ( , 2020, who do not detect significant LyC emission in their own stacking analyses. This bimodality may be caused by favorable lines-ofsight through the ISM of the host galaxy (e.g., Cen & Kimm 2015) and/or the IGM rather than by the intrinsic galaxy properties, with the small number of candidate LyC leakers corresponding to lines-of-sight with low IGM absorption.…”
Section: Contributions To the Metagalactic Ionizing Backgroundsupporting
confidence: 92%
“…Massive stars and quasars/active galactic nuclei (AGN) both produce ionizing photons, though their relative importance to the global ionizing background appears to evolve over time. Most evidence currently favors a scenario in which dwarf star-forming galaxies (SFGs) are the primary driver of hydrogen reionization (Riccoti & Shull 2000;Bouwens et al 2006;Fontanot et al 2007Fontanot et al , 2014Robertson et al 2010Robertson et al , 2015Japelj et al 2017), while AGN contributions to the ionizing background are small until z ∼ 2 -3 (Barger et al 2003;Bolton et al 2005;Cowie, Barger, & Trouille 2009;Cristiani et al 2016;Smith et al 2020). However, because these scenarios typically rely on an extrapolation of observed galaxy counts to faint absolute magnitudes unobtainable even in the deepest HST imaging, some authors have argued that quasars/AGN could produce a non-negligible or even dominant fraction of UV pho-tons during the era of reionization (e.g., Fontanot et al 2012;Madau & Haardt 2015).…”
mentioning
confidence: 99%
“…They found fesc = 0.49 ± 0.36, which they concluded to be consistent with the result by Grazian et al (2018). Smith et al (2020) used HST WFC3/UVIS imaging of the GOODS North and South and the ERS fields to examine LyC emission from galaxies and AGNs with spectroscopic redshifts at 2.26 < z < 4.3. There are 17 AGNs in their sample.…”
Section: Cowiesupporting
confidence: 82%
“…Previous studies often assumed fesc = 1 on the supposition that ionizing photons emerging from the AGN can efficiently escape into the intergalactic space. However, studies of fesc for AGNs at z = 3 − 4 based on direct measurement of their LyC have shown that this assumption could be wrong (Cristiani et al 2016;Micheva et al 2017a;Grazian et al 2018;Romano et al 2019;Smith et al 2020), although the number of AGN used in these studies is still small, except Cristiani et al (2016) and Romano et al (2019) who examined fesc of large numbers of bright quasars from SDSS at z > 3.6. Given the potential importance of AGN in reionizing the Universe, it is therefore important to better constrain the AGN fesc and its dependence on AGN luminosity.…”
mentioning
confidence: 99%
“…In recent years, direct 𝑓 esc studies have largely concentrated on two redshift windows set by available UV instrumentation -one at 𝑧 ≈ 0.3 where Lyman continuum (LyC) is accessible to HST/COS (e.g., Izotov et al 2016aIzotov et al , 2018bIzotov et al , 2021aWang et al 2019Wang et al , 2021, and another at 𝑧 ≈ 2 − 4 accessible to ground-based facilities and HST/WFC3 UVIS (e.g., Jones et al 2018;Smith et al 2020;Ji et al 2020;Meštrić et al 2020;Marques-Chaves et al 2021;Davis et al 2021;Prichard et al 2021). The 𝑧 ≈ 0.3 COS efforts were first undertaken at a time when only a handful of robust LyC leakers had been identified, and it was unclear whether LyC leakage even occurred among the 0.5𝐿 * galaxies for which 𝑓 esc measurements were feasible (e.g., Izotov et al 2016a,b).…”
Section: Introductionmentioning
confidence: 99%